2023
DOI: 10.3389/fphar.2023.1152347
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the mechanism of PSORI-CM02 in suppressing keratinocyte proliferation through the mTOR/HK2/glycolysis axis

Abstract: Hyperplasia of epidermal keratinocytes that depend on glycolysis is a new hallmark of psoriasis pathogenesis. Our previous studies demonstrated that PSORI-CM02 could halt the pathological progression of psoriasis by targeting inflammatory response and angiogenesis, but its effect(s) and mechanism(s) on proliferating keratinocytes remained unclear. In this study, we aim to identify components of PSORI-CM02 that are absorbed into the blood and to determine the effect(s) of PSORI-CM02 on keratinocyte proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Consequently, inhibiting glycolysis has emerged as a novel strategy for improving psoriasis-like skin lesions. Approaches such as gene knockout or compound inhibition of GLUT1 , 2-DG-mediated glycolysis blockade (Huang et al, 2019), pharmacological inhibition of PKM2 , and suppression of HK2 by traditional Chinese medicine PSORI-CM02 (Chapter 5, (Wang et al, 2023a)), have shown promising effects in ameliorating imiquimod-induced psoriasislike pathology in mice. However, these GLUT1-positive keratinocytes only constitute approximately 20% of the total keratinocyte population, primarily distributed in the basal layer of the psoriatic epidermis.…”
Section: Metabolic Reprogramming Of Keratinocytes Induced By Mir-31mentioning
confidence: 99%
“…Consequently, inhibiting glycolysis has emerged as a novel strategy for improving psoriasis-like skin lesions. Approaches such as gene knockout or compound inhibition of GLUT1 , 2-DG-mediated glycolysis blockade (Huang et al, 2019), pharmacological inhibition of PKM2 , and suppression of HK2 by traditional Chinese medicine PSORI-CM02 (Chapter 5, (Wang et al, 2023a)), have shown promising effects in ameliorating imiquimod-induced psoriasislike pathology in mice. However, these GLUT1-positive keratinocytes only constitute approximately 20% of the total keratinocyte population, primarily distributed in the basal layer of the psoriatic epidermis.…”
Section: Metabolic Reprogramming Of Keratinocytes Induced By Mir-31mentioning
confidence: 99%